ANALYSIS REGARDING THOSE IMPACT FROM SERVICES QUALITY AND PRODUCT QUALITY TOWARDS PURCHASE DECISIONS WHICH HAD INFLUENCE ON CUSTOMER SATISFACTION (CASE STUDY AT PT. ASTRA CREDIT COMPANIES) - Nugroho Saputra, Agung; Djumarno (Dinasti Publisher, 2020)
This research aims to discovered and analyzed those variables regarding their influence over purchasing decisions such as service quality and product quality variables and their impact towards customer satisfaction. Research population was all regular customers from PT. Astra Credit Companies Bintaro branch office while the sample amounted to 92 respondents (Slovin, 10% error tolerance). Data analysis methods used SmartPLS program which had alternative model of convariance based SEM. The results showed that: 1) Services quality had significant positive impact towards purchase decisions; 2) Product quality had significant positive influence towards purchase decisions; 3) Services quality had significant positive impact against customer satisfaction; 4) Product quality had significant positive impact on customer satisfaction; 5) Purchasing decisions had significant positive influence on customer satisfaction variables; 6) Services quality indirectly impact customer satisfaction positive and significantly through purchase decisions; and 7) Product quality indirectly impact customer satisfaction positively through purchase decisions.